16p13.11 microdeletion uncovers loss‐of‐function of a MYH11 missense variant in a patient with megacystis‐microcolon‐intestinal‐hypoperistalsis syndrome. Issue 1 (16th May 2019) - Kloth, Katja; Renner, Sina; Burmester, Gunter; Steinemann, Doris; Pabst, Brigitte; Lorenz, Birgit; Simon, Ronald; Kolbe, Verena; Hempel, Maja; Rosenberger, Georg
Abstract: Megacystis‐microcolon‐intestinal hypoperistalsis syndrome (MMIHS), a rare condition that affects smooth muscle cells, is caused by biallelic null alleles in MYH11 . We report on a girl with MMIHS in addition to growth hormone deficiency, central hypothyroidism and a tonically dilated pupil with accommodation deficit. Sanger sequencing and arrayCGH uncovered the novel heterozygous missense variant c.379C>T in MYH11 and a heterozygous 1.3 Mb deletion in 16q13.11 encompassing MYH11, respectively. Her mother carries the deletion, whereas her father is heterozygous for the c.379C>T p.(Pro127Ser) change. Proline 127 is crucial for the formation of the Adenosine triphosphate binding pocket of the MYH11 motor domain and molecular modeling indicated that p.Pro127Ser alters nucleotide binding properties. Thus, the unusual and complex clinical presentation of the patient results from compound heterozygosity for a 16p13.11 microdeletion including the entire MYH11 gene and a loss‐of‐function missense variant on the remaining MYH11 allele. In conclusion, we recommend genetic testing both for MYH11 sequence alterations and copy number imbalances in individuals with MMIHS and smooth muscle cell‐associated abnormalities in additional organs, that is, multisystemic smooth muscle dysfunction. Abstract :